P-71 Gender differences in improvements in atherosclerotic cardiovascular disease risk factors during exercise-based cardiac rehabilitation: impact of statin therapy. (18th November 2016) - Constantinou, Demitri; Gradidge, Philippe; Salmon, Richard; Schultz, William; Sperling, Laurence; Franklin, Barry; Gordon, Neil
Abstract : Studies have raised concerns that statins may attenuate favourable effects of lifestyle intervention on cardiovascular risk factors. We hypothesised that gender differences may exist in the responsiveness of risk factors to exercise-based phase 2 cardiac rehabilitation (CR) in statin-treated patients. We compared the effect of a 12-week CR program on multiple risk factors in 5734 male (age = 64±11 yrs) and 2148 female (age = 67±11 yrs) statin-treated patients (Cohort A, n = 7882). Where significant gender differences were noted, similar comparisons were made between 1516 male (age = 66±12 yrs) and 813 female (age = 64±13 yrs) CR participants not taking statins (Cohort B, n = 2329). Patients completed assessments on entry and exit from CR at 35 U.S.-based centres. Statistical analyses were performed using paired and unpaired t-tests. For Cohort A, significant (p < 0.05) improvements were observed for all risk factors in men and women, including: LDL cholesterol (males, −13.0 mg/dl; females, −10.8 mg/dl; males vs. females, p = 0.114); HDL cholesterol (males, 1.8 mg/dl; females, 1.6 mg/dl; males vs. females, p = 0.640); triglycerides (males, −17.0 mg/dl; females, −9.1 mg/dl; males vs. females, p = 0.041); BP (males, −1.8/−1.6 mmHg; females, −4.6/−2.7 mmHg; males vs. females, p < 0.001); BMI (males, −0.2 kg/m2; females, −0.2 kg/m2; males vs. females, p = 1.000); fasting glucose (males, −6.3 mg/dl; females, −4.6 mg/dl; males vs. females, p = 0.472); and weekly duration of aerobic activity (males, 122 min; females 123 min; males vs. females, p = 0.832). With the exception of BP (greater decrease in females) and triglycerides (greater decrease in males), no significant gender differences were observed. In participants not taking statins (Cohort B), similar gender differences were noted for BP but not triglycerides. Our findings suggest that: male and female statin-treated patients derive significant improvements in multiple risk factors during CR; in statin-treated CR participants, with the possible exception of triglycerides, there are either no gender differences in the magnitude of improvement or, in the case of BP, gender differences that are similar to those in patients not taking statins (greater decrease in females); and physical activity in statin treated cardiac patients should be encouraged.